A plurality of tongues giving direction to the museum - Birnbaum, Daniel 1963-; Noring, Ann-Sofi; Blom, Ina 1961-; Hessler, Stefanie 1987-; Liew, Fredrik 1978-; Obrist, Hans Ulrich 1968-; Wallenstein, Sven-Olov 1960- (Moderna Museet, 2018)
A museum is not an object, it's an activity. Exhibitions are acts, as are concerts, readings, and performances. To direct a museum is different from staging an individual exhibition. To direct a museum is to curate the entire program to establish links between shows, to create accords and tensions between art from different places and periods, between disciplines and approaches. The expanding collection is the foundation and also a battery that energizes everything else. This book highlights some of the thematic threads that run through the programs of Moderna Museet. An attentiveness towards diversities and to alternative modernisms is one such thread, and towards the great contributions of women artists. Another interest concerns the interplay between art forms: music, film, dance, poetry, design, architecture and all the disciplines that we subsume under the notion visual art. Crucial to a living museum is not only about art but also about the people that inhabits it. At the center of our activities stands not only works of art but also the artists
Keywords: Moderna Museet; Geschichte 2000-2018